Evaluation Of Antibacterial Potential of Oxazole Derivative of Haemagglutinin of Porphyromonas Gingivalis Using in Silico Molecular Docking and Admet Prediction - S.Padmaja; Parkavi Arumugam; Rajalakshmanan Eswaramoorthy (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Porphyromonas gingivalis is known to produce a lot of virulence factors that could pave their way into the gingivae and cause tissue damage either directly or indirectly, by induction of inflammation. Hemagglutinins are also considered important virulence factors, as they can be a pathway to acquire hemin, which is necessary for bacterial growth, from erythrocytesMaterials And Methods: The 2D structures (mol)of the oxazole compounds (PJ1-PJ8) were drawn using ChemDraw and analysed using Chem3D soNware. The homology modelling of the haemagglutinin protein was done using Swiss model.The graphical user interface program AutoDock Vina was used for ligand - protein docking simulations , the docking algorithm provided with AutoDock Vina was used to search for the best docked confirmation between ligand and protein. The SwissAdme and Protox online servers was used for estimating the absorption, distribution, metabolism and excretion.Statustical analysis : ANOVA(P